2012
DOI: 10.1111/j.1365-2044.2012.07118.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pre‐operative focused transthoracic echocardiography in emergency non‐cardiac surgery patients with known or risk of cardiac disease

Abstract: SummaryThis prospective observational study investigated the effect of focused transthoracic echocardiography in 99 patients who had suspected cardiac disease or were ‡ 65 years old, and were scheduled for emergency non-cardiac surgery. The treating anaesthetist completed a diagnosis and management plan before and after transthoracic echocardiography, which was performed by an independent operator. Clinical examination rated cardiac disease present in 75%; the remainder were asymptomatic. The cardiac diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 34 publications
(55 reference statements)
1
89
0
5
Order By: Relevance
“…Furthermore, the information is readily available at the patient's bedside and can be used immediately by the treating physician to guide patient management. 25 In this complex cardiac patient presenting for endoscopic sinus surgery, history, physical exam, and traditional investigations alone did not establish the diagnosis of cardiac tamponade. A focused bedside TTE performed by the anesthesiologist just prior to induction of anesthesia prevented potentially disastrous hemodynamic compromise had cardiac tamponade gone unrecognized.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the information is readily available at the patient's bedside and can be used immediately by the treating physician to guide patient management. 25 In this complex cardiac patient presenting for endoscopic sinus surgery, history, physical exam, and traditional investigations alone did not establish the diagnosis of cardiac tamponade. A focused bedside TTE performed by the anesthesiologist just prior to induction of anesthesia prevented potentially disastrous hemodynamic compromise had cardiac tamponade gone unrecognized.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20] All the studies were reported as comprehensive examinations, which was reflected in the broad diversity of diagnoses. As described previously, preoperative exams occurred immediately prior to induction of anesthesia and data from pre-assessment clinic exams were not included.…”
Section: Resultsmentioning
confidence: 99%
“…8 A prospective study of 99 patients presenting for emergency noncardiac surgery found that preoperative focused TTE screening changed the cardiac diagnosis compared with clinical examination in 67% of patients, and changed anesthesia management in 44%. 9 In another study of hip fracture surgery patients, preoperative focused TTE changed the cardiac diagnosis in 78% and the management plan in 52%, with lower mortality in the focused TTE group compared with historical controls (not a controlled study). 10 Sufficiently powered randomized controlled studies are needed to characterize populations in which preoperative screening TTE might improve outcomes.…”
Section: Discussionmentioning
confidence: 99%